SPIDER WEB ATAU SHAJARAH AL-‘ILM?: Mencari Format Ideal Kajian Hadis Integratif di Indonesia - Benny Afwadzi (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2019)
Spider Web and Shajarah  al-lmIlm are two concepth of religious and scientific integration that are popular in the Islamic Religious College (PTKIN). The first concept is owned by UIN Sunan Kalijaga Yogyakarta, while the second concept is owned by UIN Maulana Malik Ibrahim Malang. Therefore, this article focuses on reviewing integrative traditions in both concepth of integration of religion and science. This article concludes that in Spider Web, hadith are in h}adha>rah al-Nashsh which dialogue with h}adha>rah al-‘ilm and are bridged by h}adha>rah falsafah. In the concept there is also the word "sunnah" in ith normative meaning and hadith in ith historical meaning (‘Ulu>m al-Di>n), which then interacth in al-Fikr al-Isla>mi> and Dira>sat Isla>miyah in the next cluster. While in Shajarah  al-lmIlm, the Prophet's hadith became a source of knowledge along with the science of observation, experimentation, and logical reasoning. In the concept metaphor, the position of the hadith is in the trunk and learning is carried out gradually and neatly arranged. The study is carried out starting at the root first, then the stem, then branches and twigs, and ends with the fruit of knowledge, faith, good deeds, and noble character. Furthermore, this article finds some differences between integrative hadith studies in both concepth, namely first, the freer interaction of hadith scholarship in Spider Web, and the emergence of hadith as inspiration which certainly gives a new color to science in Shajarah al-‘Ilm; second, the integration of hadith which is philosophical and favored by activisth of Islamic studies in Spider Web, and the integration of hadith that is applicable and preferred by scientisth in Shajarah  al-lmIlm; and third, hadith in Islamic Studies is more developed in Spider Web, and hadith in general science is more able to develop in Shajarah al-‘Ilm.